At a general meeting of the citizens of Philadelphia, and parts adjacent, at the State-House yard in this city, on Tuesday the 25th of May 1779, General Roberdeau was unanimously requested to take the chair ; who introduced the business with the following address . (LLMC-digital (Series), 1779)
Concerning the appointment of a committee to regulate the retail prices of rum, sugar, flour, coffee and tea.